A Review of Power Domain Non-Orthogonal Multiple Access in 5G Networks - Kassir, Aiman; Dziyauddin, Rudzidatul Akmam; Mad Kaidi, Hazilah; Mohd Izhar, Mohd Azri (International Journal of Integrated Engineering, 2018)
This paper highlights the fundamentals of the strong candidate Power Domain Non-Orthogonal Multiple Access (PD-NOMA) technique, and how it can best fit the requirements of fifth Generation (5G) in practical applications. PD-NOMA ensures flexibility in radio resource to improve user’s access performance. Multiple users share the same radio resources in PD-NOMA, and therefore better spectrum efficiency can be achieved. The practical system design aspects of PD-NOMA are considered in this paper by exploring different network scenarios. Optimal performances of PD-NOMA system can be obtained by suitable power allocation schemes, with reduce the computational complexity, and advanced user pairing strategy. Theoretical formulation and solutions are also explained prior to the concept of downlink PD-NOMA. Challenges and future research windows are discussed before conclusion of this paper.